1995
DOI: 10.1037/0021-9010.80.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Applying trained skills on the job: The importance of the work environment.

Abstract: The influence of the work environment on the transfer of newly trained supervisory skills was examined. Participants were 505 supermarket managers from 52 stores. The work environment was operationalized in terms of transfer of training climate and continuouslearning culture. Climate and culture were hypothesized to have both direct and moderating effects on posttraining behaviors. Accounting for pretraining behaviors and knowledge gained in training, the results from a series of LISREL analyses showed that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
566
1
20

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(636 citation statements)
references
References 43 publications
(83 reference statements)
37
566
1
20
Order By: Relevance
“…Organizational culture learning becomes the important factor in innovative consideration since it enables an organization to anticipate and adapt with any environment change. As a matter of fact, organizational culture learning is marked as a willingness of each member in an organization to study and respect the high performance in the application of progressive learning and innovative working [24], [25]. Based on these arguments, it can be concluded hypothesis as follow:…”
Section: B the Relationship Between The Strength Of Cohesive Freedommentioning
confidence: 99%
“…Organizational culture learning becomes the important factor in innovative consideration since it enables an organization to anticipate and adapt with any environment change. As a matter of fact, organizational culture learning is marked as a willingness of each member in an organization to study and respect the high performance in the application of progressive learning and innovative working [24], [25]. Based on these arguments, it can be concluded hypothesis as follow:…”
Section: B the Relationship Between The Strength Of Cohesive Freedommentioning
confidence: 99%
“…Whilst structural aspects were recognised as important to professional development only towards the end of the year, informal learning was seen as more important during training, including observing and working alongside experienced practitioners, as other studies of work-based learning have found (Tracey et al, 1995;Eraut et al, 2000).…”
Section: Key Factorsmentioning
confidence: 99%
“…It was in school that all five types of 'on the job' training identified by de Jong (1997) Structural support and training were provided by schools through their procedures, policies and practices, such as planning, behaviour management and assessment. This was usually led by the headteacher, a key figure in promoting good practice in the primary school (Ofsted, 2002b;Sturman, 2003); strong leadership is identified as a major factor affecting learning in the workplace (Tracey et al, 1995;Eraut et al, 2000). Many GTP trainees were based in well organised schools, providing good models of primary practice (as identified by the LEA and in Ofsted reports), which enhanced their own professional development.…”
Section: School-based Training and Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, researchers have focused on the role that climate plays in motivational processes for individual and team outcomes (Ashkanasy, Wilderon, & Peterson, 2000;Kozlowski & Klein, 2000). Specific domains of climate that have been studied include service climate (Schneider, Parkington, & Buxton, 1980), innovation climate (Anderson & West, 1998), safety climate (Hofmann & Stetzer, 1996), transfer to training climate (Tracey, Tannenbaum, & Kavanagh, 1995), procedural justice climate (Naumann & Bennett, 2000), and affective climate (De Rivera, 1992). In general, this research has shown that climate accounts for substantial variance in work attitudes and behaviors.…”
Section: The Moderating Role Of Affective Climatementioning
confidence: 99%